Medical Histopathology Laboratories: Remote Teaching in Response to COVID-19 Pandemic - Sharma, Ramaswamy (Acad Pathol, 2021)
The COVID-19 pandemic required the rapid conversion of medical school curricula to virtual instruction. Prior to the crisis, histopathology teaching laboratories at UT Health San Antonio included completion of an Individual Laboratory Quiz before the laboratory session, a Team Application Exercise released and completed during the laboratory session with guidance from faculty, and a graded Team Laboratory Quiz at the end of the laboratory session. Adaptation of this interactive, in-person activity to a fully online platform included releasing the Team Application Exercise earlier to provide ample time for students to work virtually with their teams, conducting laboratory sessions using Microsoft Teams, with 5 to 6 teams led by a single instructor, and requiring the Team Laboratory Quiz to be taken individually for ensuring quiz security and test integrity. For incentivizing collaboration while completing the Team Application Exercise, the final score was either the student’s individual score on the Team Laboratory Quiz or their team’s average, whichever was higher. Comparison of student scores on the modified Team Laboratory Quiz to Team Laboratory Quiz scores using the earlier laboratory format prior to COVID-19 showed a significant decline; however, scores on other weekly quizzes or examinations were unaffected. Students welcomed the early release of Team Application Exercise and easier access to faculty but indicated that the modified Team Laboratory Quiz decreased peer-teaching and learning experience and increased anxiety. Faculty indicated the loss of personal interaction with students as a major theme. These data suggest that novel pedagogical approaches are required for online histopathology instruction to accommodate differences in learning styles while maintaining the benefits of team collaboration.